Comparative biomechanics of the Pan and Macaca mandibles during mastication: finite element modelling of loading, deformation and strain regimes. Issue 5 (13th August 2021) - Smith, Amanda L.; Robinson, Chris; Taylor, Andrea B.; Panagiotopoulou, Olga; Davis, Julian; Ward, Carol V.; Kimbel, William H.; Alemseged, Zeresenay; Ross, Callum F.
Abstract : The mechanical behaviour of the mandibles of Pan and Macaca during mastication was compared using finite element modelling. Muscle forces were calculated using species-specific measures of physiological cross-sectional area and scaled using electromyographic estimates of muscle recruitment in Macaca . Loading regimes were compared using moments acting on the mandible and strain regimes were qualitatively compared using maps of principal, shear and axial strains. The enlarged and more vertically oriented temporalis and superficial masseter muscles of Pan result in larger sagittal and transverse bending moments on both working and balancing sides, and larger anteroposterior twisting moments on the working side. The mandible of Pan experiences higher principal strain magnitudes in the ramus and mandibular prominence, higher transverse shear strains in the top of the symphyseal region and working-side corpus, and a predominance of sagittal bending-related strains in the balancing-side mandible. This study lays the foundation for a broader comparative study of Hominidae mandibular mechanics in extant and fossil hominids using finite element modelling. Pan 's larger and more vertical masseter and temporalis may make it a more suitable model for hominid mandibular biomechanics than Macaca .